METHODOLOGY FOR DEVELOPING COMPETENCES OF FUTURE FOREIGN LANGUAGE TEACHERS BASED ON INNOVATIVE TECHNOLOGIES. - Iroda Ilkhamova; Utkir Muradov; Gulshada Damirova; Zumrat Khudoyberdiyeva (The Bioscan, 2024)
In this article, the development of professional competencies (reading and writing skills) of future foreign language teachers based on innovative technologies and forms and the effectiveness of reading and writing skills in classroom training using PRES formula, freewriting and jigsaw methods Reinforcement and analysis of strategies for teaching reading and writing skills.